SISTEM PEMESANAN MAULANY’S CATHERING BERBASIS DESKTOP - Pauziah, Ulfa; Isnain, Nasrulloh; Rahmatika, Rahmatika (Universitas Majalengka, 2023)
The research objective for designing a Desktop-Based Maulany's Cathering Ordering System is to quickly improve customer service. The research method used in this research is a qualitative method with a descriptive approach. Descriptive research is research to collect information regarding the status of existing symptoms, namely the condition of the symptoms according to what they were at the time the research was carried out. The results of the design of the Maulany's Cathering Ordering System have been carried out, so the author can have detailed conclusions as follows. This application has been computerized which can be produce accurate data and reports